Magnesium phosphate cement formulated with low grade magnesium oxide with controlled porosity and low thermal conductivity as a function of admixture. Issue 13 (October 2016) - Niubó, M.; Formosa, J.; Maldonado-Alameda, A.; del Valle-Zermeño, R.; Chimenos, J.M.
Abstract: Magnesium phosphate cement (MPC) formulated with low-grade magnesium oxide (LG-MgO) can be better considered as sustainable MPC (sust-MPC). Among other properties, sust-MPC could be used as building material for constructive elements because of its acoustic and thermal insulation properties. Porosity and thermal conductivity are two important parameters that have a significant influence on thermal insulation properties. In this regard, this work aimed to obtain a highly porous sust-MPC with enhanced properties for thermal insulation. To this end the percentage of porosity as a function of both the amount of set-retarding admixture and the kneading water needed was assessed using a statistical design of experiments (DoE) approach. Additionally, thermal conductivity was also evaluated with respect these two factors. Last but not least, an optimized dosage was sought in order to maximize the percentage of porosity while achieving the lowest thermal conductivity. According to the results obtained, the statistical method successfully predicted the effects of variables on the final properties. Hence, a model that explains the overall behavior of the system was successfully attained. The obtained model predicts the porosity and the thermal conductivity of sust-MPC by means of the mixture dosage. Consequently, the present work demonstrates that it is possible to control the porosity in order to diminish thermal conductivity.